Councils of State in Europe in their advisory and legislative functions: France, Belgium, Spain, Italy and Luxembourg. (2nd January 2023) - Farhat, Nadim; Poirier, Philippe
ABSTRACT: This special issue explores the Council of State as an institution at the heart of the workings of the political-administrative system of many European states. More specifically, it dwells on the consultative and legislative functions of the Council of State as an institution. This special issue shows through the analysis of the cases of five European countries (France, Belgium, Spain, Italy and Luxembourg) in what ways the consultative action of the Council of State, while revealing its dual technical and political nature, assumes a role of neutrality and expertise which is authoritative within the debates that agitate parliamentary democracies. Examining the Council of State from the angle of its advisory function, as well as the dynamics and pressures to which it is subjected, makes it possible to identify both the evolution and the constraints that affect the construction of the law undertaken by legislative assemblies and governments and more generally the development of state standards.